Firm exporting and productivity: what if productivity is no longer a black box. Issue 2 (2nd July 2016) - Vu, Huong Van; Holmes, Mark; Tran, Tuyen Quang; Lim, Steven
ABSTRACT: This paper uses Vietnamese firm-level data to examine the relationship between firm productivity and exporting. In particular, this paper shows that more productive firms are more likely than less productive firms to export, consistent with the extensive prior literature. However, this paper finds no evidence that exporting affects productivity, which can be decomposed into technical efficiency change, technological progress, and scale change. Thus, the findings support a large role of self-selection in accounting for export decision, but little gain from learning-by-exporting in the case of Vietnamese Small medium sized enterprises (SMEs). These findings imply that export promotion policies may not be effective unless accompanied by strategies to help SMEs become more productive.